Can Off-Training Physical Behaviors Influence Recovery in Athletes? A Scoping Review - Izzicupo, Pascal; Di Baldassarre, Angela; Ghinassi, Barbara; Reichert, Felipe Fossati; Kokubun, Eduardo; Nakamura, Fábio Yuzo (Frontiers in Physiology, 2019)
Recently, the attention on recovery in sport has increased enormously although there is lack of scientific evidence on the role of lifestyle in terms of movement (i.e. physical behaviors [PBs]). Although there has been a proliferation of published articles focused on sleep, a small number of studies assessed the levels of physical activity (PA) and sedentary behavior (SB) in athletes. Furthermore, these types of research articles generally investigated only few isolated aspect (e.g. off-training PA, sitting time, sleep) rather than on the combined effect of 24-h PBs. Furthermore, differences regarding participants, instruments and technical specifications of the adopted devices, prevent the generalization of results, and these factors need to be addressed by researchers. On that basis, the aims of this scoping review were to answer to the following scientific questions: 1) How active/inactive are competitive athletes out of training? 2) Does off-training PBs affect recovery, performance, health, physical fitness, and career? 3) What strategies can be implemented to improve recovery using off-training PBs, apart from sleep? From 5,046 potentially relevant articles, nine were eligible for inclusion in this review. The main issues identified related to the heterogeneity concerning the types of sports, age category, gender, competitive level, sample size, and instruments/devices adopted, the paucity of studies investigating the effects of PBs while awake (i.e. PA and SB) on recovery, and the lack of experimental designs that manipulated PBs while awake to accelerate recovery or improve performance. Furthermore, PA and SB domains were rarely investigated, while no research articles focused on